The influence of Zona1 training on the periodization of the race - Andres, Leandro Rubio (Seven Editora, 2024)
The purpose of this study is to examine the importance and impact of zonal workouts – a level of training with low to moderate intensity, which focuses on increasing cardiovascular endurance and improving aerobic metabolism. Through this research, we seek to understand how this methodology can improve the performance of runners in the long term. Running is a complex sport that requires a proper combination of speed, endurance, strength, and strategy. While it's commonly thought that running faster in workouts will lead to better performance during races, recent studies suggest that integrating training periods into zone1 may be equally or even more beneficial. Using a quantitative and qualitative methodological approach, this study aims to analyze empirical data from professional and amateur runners to provide insights into the benefits of zone1 workouts in improving running performance. The research will also explore the physiological principles behind this training methodology to give a scientific insight into the implications of zone training1. It is hoped that the results of this study will contribute to the understanding of the importance of different types of training in running, encouraging athletes and professionals in the area to consider the inclusion of zonal training1 in their training programs. DOI:https://doi.org/10.56238/sevened2024.010-020